Spontaneous Visual Imagery During Meditation for Creating Visual Art: An EEG and Brain Stimulation Case Study - Luft, Caroline Di Bernardi; Zioga, Ioanna; Banissy, Michael J.; Bhattacharya, Joydeep (Frontiers in Psychology, 2019)
Experienced meditators often report spontaneous visual imagery during deep meditation in the form of lights or other types of visual images. These experiences are usually interpreted as an “encounters with light” and gain mystical meaning. Contrary to the well-studied intentional and controlled visual imagery, spontaneous imagery is poorly understood, yet it plays an important role in creativity of visual artists. The neural correlates of such experiences are indeed hard to capture in laboratory settings. In this case study we aimed to investigate the neural correlates of spontaneous visual imagery in an artist who experiences strong visual imagery during meditation. She uses these images to create visual art. We recorded her EEG during 7 meditation sessions in which she experienced visual imagery episodes (visions). To examine the functional role of the neural oscillations we also conducted 3 separate meditation sessions under different transcranial alternating current (tACS) brain stimulation: alpha (10 Hz), gamma (40 Hz) and sham. We observed a robust increase in occipital gamma power (30-70 Hz) during the deepest stage of meditation across all sessions. This gamma increase was consistent with the experience of spontaneous visual imagery: higher during visions compared to no visions. Alpha tACS was found to affect the contents of her visual imagery, making them sharper, shorter and causing more visions to occur. The artist reported that these sharp images were too detailed to be used in her art. Interestingly, gamma and sham stimulation had no impact on her the visual imagery contents. Our findings raise the hypothesis that occipital gamma might be a neural marker of spontaneous visual imagery, which emerges in certain meditation practices of experienced meditators.